Effects of comprehensive income reporting on judgments of non–professional investors - Sajnóg, Artur (Raportowanie wyniku całkowitego w opinii nieprofesjonalnych inwestorów, 2020)
This study examines the usefulness of comprehensive income as important information in the financial statements for the purpose of making investment decisions by Polish non–professional investors. The discussed research problem was realised in two parts. The first part depicts mainly theoretical reflections on the concept of comprehensive income and its strengths and weaknesses for investors. The second part outlines the survey results on the usefulness of comprehensive income in the opinions of individual investors which show that respondents assessed comprehensive income (including its components) as important for making investment decisions. At the same time, users of financial statements were quite unanimous that the implementation of comprehensive income to the financial reporting system increased the transparency of information and allowed for more accurate financial analyses of joint stock companies. In many cases, comprehensive income was considered to be a better measure of economic efficiency and market value than ‘traditional’ net income
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 67-77
Keywords: comprehensive income; income reporting; net income; investors; investment decisions; wynik całkowity; raportowanie wyniku; wynik netto; inwestorzy; decyzje inwestycyjne